2018
DOI: 10.1007/s10549-018-4845-4
|View full text |Cite
|
Sign up to set email alerts
|

Real-time, intraoperative detection of residual breast cancer in lumpectomy cavity walls using a novel cathepsin-activated fluorescent imaging system

Abstract: The LUM Imaging System allows rapid identification of residual tumor in the lumpectomy cavity of breast cancer patients and may reduce rates of positive margins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
89
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(89 citation statements)
references
References 25 publications
0
89
0
Order By: Relevance
“…Use of this system for breast cancer lumpectomies has been previously described. 21 The imaging probe has a 2.6-cmdiameter circular field of view and an outer diameter of 3.1 cm with an angled neck that facilitates contact with lateral and anterior cavity walls.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Use of this system for breast cancer lumpectomies has been previously described. 21 The imaging probe has a 2.6-cmdiameter circular field of view and an outer diameter of 3.1 cm with an angled neck that facilitates contact with lateral and anterior cavity walls.…”
Section: Methodsmentioning
confidence: 99%
“…LUM015 fluorescent signal was correlated with histopathology on hematoxylin and eosin stained slides. 22 The study started with a tumor detection algorithm established from ex vivo imaging data from our Phase 1 19 and pilot 21 studies. This was used to (1) establish the tumor detection threshold for each patient during their intraoperative imaging session and (2) guide the surgeon in excising additional tissue.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cathepsin-targeting probes have been investigated for use in tumor detection and fluorescence-guided tumor surgical resection in preclinical studies or early-phase clinical trials [9,10,16,[38][39][40][41][42][43][44]. These probes are based on fluorescently labeled inhibitors or substrates.…”
Section: Discussionmentioning
confidence: 99%
“…However, the frozen section cannot be completely omitted in breast conserving surgery to evaluate the status of surgical margins. Several studies reported the results of fluorescence-guided margin assessment in breast conserving surgery to compensate for this disadvantage [25][26][27][28]. However, a specific device and agent are necessary to conduct such studies.…”
Section: Discussionmentioning
confidence: 99%